2020
DOI: 10.3390/ijms21124301
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of miR-941 in Circulating CD14+ Monocytes Enhances Osteoclast Activation via WNT16 Inhibition in Patients with Psoriatic Arthritis

Abstract: Psoriatic arthritis (PsA) is a destructive joint disease mediated by osteoclasts. MicroRNAs (miRNAs) regulate several important pathways in osteoclastogenesis. We profiled the expression of miRNAs in CD14+ monocytes from PsA patients and investigated how candidate microRNAs regulate the pathophysiology in osteoclastogenesis. The RNA from circulatory CD14+ monocytes was isolated from PsA patients, psoriasis patients without arthritis (PsO), and healthy controls (HCs). The miRNAs were initially profiled by next-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In addition, MiR-21-5p upregulation in one of the mi-RNA signatures was identified in patients with active PsA and possibly might be used in the monitoring of response to treatment [32]. A similar role was suggested for miR-941, which was found in CD14+ monocytes [33].…”
Section: Genetic and Pharmacogenetic Biomarkersmentioning
confidence: 83%
“…In addition, MiR-21-5p upregulation in one of the mi-RNA signatures was identified in patients with active PsA and possibly might be used in the monitoring of response to treatment [32]. A similar role was suggested for miR-941, which was found in CD14+ monocytes [33].…”
Section: Genetic and Pharmacogenetic Biomarkersmentioning
confidence: 83%
“…In research of human chronic inflammatory diseases, OC numbers are often consistent with total resorption, which is higher in RA versus HD PBM [ 25 , 69 ], in RA versus OA SFM [ 81 ], in PsA versus HD PBM [ 26 , 71 , 82 , 83 ] and in CD versus HD PBM [ 84 ]. Good concordance has been reported in comparison of erosive versus non-erosive RA, where both differentiation and resorption were higher in erosive RA PBM [ 69 ].…”
Section: Methods Of In Vitro Osteoclastogenesismentioning
confidence: 99%
“…Several studies have demonstrated differential expression of miRNAs that had previously been found to be altered in blood and synovial fluid samples from RA patients. For example, miRNA-146a and miRNA-941 expression is known to be upregulated in circulating CD14+ monocytes from PsA patients [56,57]. Pelosi et al identified in blood cells specific miRNA signatures associated with active and non-active disease.…”
Section: Transcriptional Regulation Via Non-coding Rnasmentioning
confidence: 99%